Emprego de técnicas de representação do conhecimento como forma de apoio à engenharia de requisitos - Kroth, Eduardo (2012)
The Requirements Engineering is fundamental part of the process of software development. Even if a program uses the most advanced technologies and has the best source code, it is not useful if it does not meet your requirements. The large number of failures occurring in software projects, attributed to deficiency of capturing and analyzing their requirements emphasize the importance of this area. In this work, we used knowledge representation in order to store the knowledge about the requirements of a project and then use it as a support to the capture and analysis of requirements. In addition, techniques of similarity were applied on the requirements, to ensure they are contextualized and mutually consistent.